2019
DOI: 10.1080/15592294.2019.1581594
|View full text |Cite
|
Sign up to set email alerts
|

Maternal pre-pregnancy obesity, offspring cord blood DNA methylation, and offspring cardiometabolic health in early childhood: an epigenome-wide association study

Abstract: Pre-pregnancy obesity is an established risk factor for adverse sex-specific cardiometabolic health in offspring. Epigenetic alterations, such as in DNA methylation (DNAm), are a hypothesized link; however, sex-specific epigenomic targets remain unclear. Leveraging data from the Newborn Epigenetics Study (NEST) cohort, linear regression models were used to identify CpG sites in cord blood leukocytes associated with pre-pregnancy obesity in 187 mother-female and 173 mothermale offsprings. DNAm in cord blood was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 69 publications
4
51
0
Order By: Relevance
“…Mechanisms for oxidative stress resulting from increased maternal BMI are also well known 35 and are driven by production of proinflammatory chemokines, adipokines (ie, leptin), and innate inflammatory cytokines (ie, TNF-a and IL-6) from adipose tissue. Prenatal exposures to maternal smoking, 36 acetaminophen intake, 37 and greater BMI 38 have all been linked to altered DNA methylation profiles, suggesting that the influence of these pro-oxidant fetal exposures on disease outcomes might be mediated by alterations in the epigenome.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms for oxidative stress resulting from increased maternal BMI are also well known 35 and are driven by production of proinflammatory chemokines, adipokines (ie, leptin), and innate inflammatory cytokines (ie, TNF-a and IL-6) from adipose tissue. Prenatal exposures to maternal smoking, 36 acetaminophen intake, 37 and greater BMI 38 have all been linked to altered DNA methylation profiles, suggesting that the influence of these pro-oxidant fetal exposures on disease outcomes might be mediated by alterations in the epigenome.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, early embryogenesis is a critical period for the establishment of the epigenome [14]. Maternal obesity may influence the placenta and offspring epigenetic landscape [15,16]. Ge et al found that DNA methylation in differential methylation regions of Peg3 is altered in spermatozoa of offspring from obese mothers, but is not affected in spermatozoa of offspring from diabetic mothers [17].…”
Section: Epigenomementioning
confidence: 99%
“…First, estrogen has been shown to have anti‐inflammatory properties and may reduce cytokine exposure as well as protect against fat accumulation in the brain of female fetuses specifically (Argente‐Arizón et al, ; Kim, Young, Grattan, & Jasoni, ; Tiwari‐Woodruff & Voskuhl, ; Zhu et al, ). Second, because an adverse in utero environment may result in altered epigenetic modifications to the X‐chromosome and could specifically impact X‐linked genes important for brain development, females may be more protected by having two X‐chromosomes (Cox et al, ; Glendining & Jasoni, ; Martin et al, ; Schellong et al, ).…”
Section: Introductionmentioning
confidence: 99%